2017
DOI: 10.4088/jcp.15m10206
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Disturbance Predicts Posttraumatic Stress Disorder and Depressive Symptoms

Abstract: Sleep disturbance, PTSD, and depressive symptoms were prevalent and persistent in adolescents at 12 and 24 months after exposure to the Wenchuan earthquake. Sleep disturbance predicts the development and persistence of PTSD and depressive symptoms. Early assessment and treatment of sleep disturbance may be an important strategy for prevention and intervention of PTSD and depression in adolescent trauma survivors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
72
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(79 citation statements)
references
References 0 publications
7
72
0
Order By: Relevance
“…First, all measures in this study were based on adolescents' self‐report. It is noteworthy that other researchers have used self‐report as the most efficient low‐cost way to collect sleep quality in large samples . There is evidence that subjective measures of sleep from children and adolescents had moderate to high correlations with objective measures (rs = .47 ∼ .99, p < .05) and are preferred over parent reports of sleep .…”
Section: Discussionmentioning
confidence: 99%
“…First, all measures in this study were based on adolescents' self‐report. It is noteworthy that other researchers have used self‐report as the most efficient low‐cost way to collect sleep quality in large samples . There is evidence that subjective measures of sleep from children and adolescents had moderate to high correlations with objective measures (rs = .47 ∼ .99, p < .05) and are preferred over parent reports of sleep .…”
Section: Discussionmentioning
confidence: 99%
“…Depression and sleep disturbance are likely to have a bidirectional relationship (Harvey 2006). A study among 3186 Chinese adolescents aged 13-18 years demonstrated that those who had depressive symptoms were also at a higher risk of sleep disturbance (Guo, Deng et al 2014), and another cohort study found that sleep disturbance among Chinese adolescents predicted the development and persistence of depressive symptoms (Fan, Zhou et al 2016). There is also evidence to suggest that insomnia is an independent risk factor for first and recurrent episodes of depression (Riemann, Berger et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…14,15 It has been reported in a recent study that 63.9% of Chinese nurses working in general hospital experienced disturbed sleep. 16 Sleep disturbance is associated with depressive status 17 and correlated with increased negative emotional state, 18 which may in turn have significant influence on their mental status, further worsening depressive symptoms. [19][20][21] Researchers have proposed to apply the Conservation of Resources (COR) theory into studies of work and stress in organizational circumstances 22 and found that increase of resource is a critical component of the management of stress in organizations and successful prevention and can promote occupational well-being.…”
Section: Introductionmentioning
confidence: 99%
“…25 Recovery experience may help nurses to combat negative emotions, reduce occupational fatigue and exhaustion, and relieve the symptoms of sleep disturbance through positive adjustment process of "psychological detachment, relaxation, mastery experiences and control" to manage the stressful situations in clinical settings, and ultimately may attenuate depressive symptoms. 17,25,[27][28][29][30][31] There has been a paucity of studies on the relationships among depressive symptoms, recovery experience, and sleep disturbance among female nurses in Chinese public hospitals. The aim of this study is to investigate female nurses' depressive symptoms and examine the relationship between depressive symptoms, recovery experience, and sleep disturbance.…”
Section: Introductionmentioning
confidence: 99%